THE RELATION OF TINA NGATA’S MATRIARCHATE ROLE IN SPIRITUAL ECOFEMINISM PERSPECTIVES - Nisbah Nisbah (State Institute of Islamic Studies (IAIN) Palu, 2019)
The perspective approach of Spiritual Ecofeminism in studying the role of women in indigenous communities is a limited study. The role of Tina Ngata as subjects is set up, maintain and manage the entire social activity in relation between human and human and between human and nature to show the existence of women as the center and core of life in relation of matriarchal role. The role and position of Tina Ngata as guardians of the Katuwua and Hintuwua values in the MHA Kulawi or Sintuvu Posarara values in the Kaili tribe is a manifestation of concern for nature so that there will be ecological sustainability and the continued availability of natural resources that support the needs of human life. Tina Ngata in carrying out her social functions with the strength of leadership, wisdom, talents, authority and charisma is needed to maintain and manage the relationship between each individual member of the community in social life. Philosophically, the role of Tina Ngata devotes herself to maintaining social life with a sense of caring and commitment in overcoming social problems and the ability to maintain the balance of nature in managing nature (forests) and the social environment is the interpretation of universal goals as affirmed in the perspective of ecofeminism spirituality.